Transformational Leadership and Turnover Intention in the Context of SMEs: Mediating Role of Work Engagement and Job Satisfaction - Thahrim, Muhammad; Amarullah, Dudi; Damayanti, Ririn (Indonesian Journal Publisher, 2024)
Employee turnover has become a problem for many business owners because it affects the sustainability of the business. This research was intended to explore the role of transformational leadership in determining SME employee turnover intention with job satisfaction and work engagement as mediators. Using purposive sampling, two hundred twenty-seven responses were obtained by distributing questionnaires to SME employees. The PLS-SEM application was used to analyze the collected data. The results revealed that transformational leadership positively affects work engagement and job satisfaction. On the other hand, transformational leadership negatively affects turnover intention. In addition, the results also reveal that work engagement and job satisfaction negatively affect turnover intention. Furthermore, work engagement and job satisfaction also intercede the impact of transformational leadership on turnover intention. This research provides essential implications for managing human resources owned by SMEs.